Home - Morrison, Toni. (New York : Knopf, 2012)
"The story of a Korean war veteran on a quest to save his younger sister"--Provided by publisher.
Booklist starred
Kirkus Starred
Pub Weekly
Booklist starred, March 2012
Kirkus Starred, March 2012
Pub Weekly, March 2012
Keywords: African American veterans -- Fiction; African Americans -- Fiction; Brothers and sisters -- Fiction; African American veterans -- Fiction; African Americans -- Fiction; FICTION / Literary; Siblings -- Fiction; Georgia -- Fiction; Georgia -- Fiction